Enteropathy in Zambians with HIV related diarrhoea: regression modelling of potential determinants of mucosal damage. Issue 6 (1st December 1997) - Kelly, P; Davies, S E; Mandanda, B; Veitch, A; McPhail, G; Zulu, I; Drobniewski, F; Fuchs, D; Summerbell, C; Luo, N P; Pobee, J O M; Farthing, M J G
Abstract : Background —AIDS is characterised by small intestinal mucosal damage, but its aetiopathogenesis is poorly understood. Enteric infections in Africa differ from those in northern countries, where protozoan infections have been associated with severe enteropathy in AIDS patients. Aims —To characterise enteropathy in Zambian AIDS patients compared with local controls, and to assess relative contributions of enteric infection, nutritional impairment, and immune dysfunction. Methods —Computer aided mucosal morphometry of small intestinal biopsy specimens from 56 HIV infected Zambians with persistent diarrhoea and 26 diarrhoea free controls, followed by regression modelling. Results —Patients with HIV related diarrhoea had reduced villous height and increased crypt depth compared with controls. There was no difference between HIV positive and negative controls. In regression models applied to AIDS mucosal measurements, villous height and crypt depth were related to nutritional parameters and to serum soluble tumour necrosis factor receptor p55 concentration. Crypt depth was also related to lamina propria plasma cell count. Intestinal infection was found in 79%, which consisted predominantly of microsporidia in 34%, Isospora belli in 24%, and Cryptosporidium parvum in 21%, but detection of these enteropathogens was not related to severity of enteropathy. Conclusions —Nutritional and immune disturbances were associated with enteropathy, accounting for over one third of the variation in mucosal morphometric parameters.